THE ROLE OF ENGLISH AS A GLOBAL LINGUA FRANCA - Diyora Jalilovna Narimanova (Modern American Journals, 2025)
English has evolved from a colonial language to a global lingua franca, shaping communication in diplomacy, business, science, education, and digital spaces. This paper examines the factors contributing to the rise of English as a global lingua franca, its impact on intercultural communication, and the challenges it poses for linguistic diversity and equality. By exploring historical, socio-political, and economic contexts, the paper argues that while English facilitates global exchange, it also reinforces linguistic hierarchies and cultural dominance. The paper draws on examples from international organizations, academic research, and global media to illustrate the multifaceted role of English today.
Keywords: English language, global lingua franca, intercultural communication, linguistic imperialism, multilingualism, language policy.